'Essentially sound and fundamental': Historicizing the logic of deterrence in the counterforce debate. (September 2015) - Szalai, András
Faced with the strategic uncertainties of the early nuclear age, the US Air Force (USAF) turned to civilian experts (defense rationalists) for help. Although the two communities shared the perception that science-based policies were required, the marriage of two distinct traditions – military and scientific – was not without conflict. Using an interpretivist approach, this article investigates this problematic reconciliation. It construes the realm of nuclear strategy-making as an interpretive enterprise where a multitude of ideas competed. Experts in this environment influenced policy decisions by rendering their ideas persuasive for their military 'patrons' through narrative framing devices. Within this conceptualization, bureaucratic dilemmas faced by the patron offered opportunities for experts to establish metaphorical correspondence between their tradition and the patron's tradition. Such correspondence then lent ideas legitimacy and encouraged organizational support. As an illustration, an analysis is conducted on the role that hallmark RAND ideas on war limitation played in the so-called 'counterforce' debate in the early 1960s. This case suggests that the lasting impact of deterrence ideas had less to do with their correspondence to reality, than with their versatility as carriers of constructed 'scientific' and 'rational' storylines that gained traction within the USAF.